The effect of traffic load on using XCAST based routing protocol in wireless ad hoc networks - Alzyoud, F.Y.; Mohamad, I.J.; Tat-Chee Wan (2009 7th International Conference on Information, Communications and Signal Processing, 2009)
Wireless ad hoc networks are a collection of mobile nodes spreading over a defined geographical area, enabling realtime collaborative applications such as push-to-talk and VoIP. Unfortunately, wireless ad hoc networks suffer from limited bandwidth and QoS constraints. A proposed eXplicit MultiCAST (XCAST) based routing protocol (P-XCAST) is presented in this paper to support team-based communications in wireless ad hoc networks. XCAST is well suited for supporting a large number of small groups effectively, in comparison with multicast based protocols. However, since XCAST was initially designed for wired networks, it was not optimized for wireless ad hoc network use. The proposed P-XCAST protocol enhances XCAST for ad hoc network use by having a Group Route Request mechanism to build the network topology, and route data packets containing the list of destinations for a given group in the XCAST header, by classifying the destinations according to similarities in their next hop neighbors and hop counts. A single data packet is XCASTed in lieu of sending n Unicast data packets to n destinations with the same next hop neighbor. In this paper, P-XCAST was tested using different traffic load values that are used with different codec to investigate its performance in various group sizes. The results of simulation show better QoS performance compared with other routing protocols.